Development of Fitness Education Model Based on FITT Method in Electronic Book Physical Education Learners In Schools Intermediate First - guntur, aep; Resty Gustiawati; Febi Kurniawan (UNIB Press, 2024)
Development of an electronic book-based fitness education model aims to improve the effectiveness of physical education learning in Junior High Schools by applying the FITT principle (Frequency, Intensity, Time, and Type). This model is designed to integrate electronic book technology in learning with the aim of increasing student motivation, participation, and overall physical fitness through the FITT approach. This study uses the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation) to design, test, and evaluate the FITT-based learning model. At the analysis stage, a needs analysis and literature study were carried out, including sources from electronic books, related to challenges in physical education in junior high schools by considering the FITT principle. The design stage includes designing a learning model that combines the principles of FITT-based physical education with electronic book technology. At the development stage, a prototype of the FITT-based model was developed which was tested in several schools. The implementation stage involves the application of the FITT-based model in real learning, and the evaluation stage is carried out to assess the effectiveness, efficiency, and level of student acceptance of the FITT-based learning model that was developed. The results of the study indicate that the electronic book-based fitness education model using the FITT approach can increase student involvement in physical activities, as well as provide a positive contribution to improving physical fitness. This model also shows potential for wider application in schools as part of innovation in FITT-based physical education learning.